The Relationship of Father's Involvement in Parenting with The Independent Level of Children Daily Living Activity in Children with Mental Retardation in SLB-C TPA Jember Regency - Elsiana Dwi Cahya; Latifa Aini Susumaningrum; Kholid Rosyidi Muhammad Nur (KHD-Production, 2021)
The mental retardation is one of the psychological limitations which have a characteristic level of intelligence (IQ) of approximately 70 or lower and experience difficulties in carrying out daily activities, communication, the ability to make self-decisions, recreation, work, health, and security. The method used in this research is a correlational study with a cross sectional approach with a total of 67 respondents using total sampling. The questionnaire given to analyze the involvement of fathers in parenting is the involvement of fathers in parenting by the NOC and to analyze the level of independence of daily living activities in children with mental retardation is Waissman-Activity daily living (W-ADL). The Spearman test was carried out to analyze objectively in this study. The results obtained in this study were as many as 58 (86.6%) fathers admitted that they were involved in caring for their children, and as many as 47 children (70.1%) based on their father's recognition that they had a high degree of independence in carrying out daily activities (r; -0.258; p- value = 0.035). This study recommends father and mother to train, guide, and educate children with mental retardation to improve children's abilities, especially in carrying out daily activities. Keywords: Father Involvement, Independence Activity daily living, Children With Mental Retardation